Clozapine induced akathisia: A case report and review of the evidence - Grover, Sandeep (Indian J Pharmacol, 2015)
Clozapine is a second-generation antipsychotic medication, which is mostly used in patients with treatment resistant schizophrenia. It is considered to be associated with lower incidence of extrapyramidal side-effects. Akathisia is considered to be a rare side-effect of clozapine. In this report, we describe a patient who developed akathisia while receiving clozapine and review the literature. Existing literature suggests that except for few initial reports, data suggests that clozapine is in general associated with lower incidence of akathisia compared to first generation antipsychotics. Data comparing clozapine with other atypical antipsychotics is equivocal.